OP0072 IDENTIFYING POLYMYALGIA RHEUMATICA RELAPSE AND ITS ASSOCIATIONS IN A RETROSPECTIVE COHORT. (2nd June 2020) - Bolhuis, T.; Marsman, D.; Den Broeder, N.; Van den Hoogen, F.; Den Broeder, A.; Van der Maas, A.
Abstract : Background: Polymyalgia rheumatica (PMR) relapse occurs frequently when tapering glucocorticoids (GC) 1 . Some risk factors for varying definitions of relapse have been identified, although with conflicting results 2 . Identification of relapse and its associations can help identify patients in need of tighter follow up or additional medication. Objectives: To identify PMR GC-taper related relapse (proportion 1 and 2 years after starting treatment and per year of treatment) and candidate predictors, for a future prediction model. Methods: In a retrospective cohort of new PMR patients, visiting our hospital from April 2008 – January 2018, all visits > 30 days after starting GC treatment and with > 2.5mg oral prednisolone were used to identify substantial relapses. Relapse was defined in two ways: rheumatologist judgement (RJ) and treatment intensivation (TI). Agreement between RJ and TI at visits was assessed. TI relapse was used going forward for treatment based prediction. The proportion of relapsers after 1 and 2 years (cumulative incidence) and the amount of relapses per year of treatment (incidence rate (IR)), were assessed. Unadjusted associations with candidate predictors, present when starting GC treatment, were assessed using logistic and Poisson regression respectively. Results: Data from 417 patients was used (figure 1 ). Relapse occurred at 405 and 325 (of 2455) visits based on RJ and TI respectively. TI relapse (cumulative incidence) after 1 and 2 years was 134 (32%) and 184 (44%) and IR was 0.35 per patient year. Unadjusted significant associations for the cumulative incidence were CRP and ESR at baseline, and symptom duration before treatment (table 1 ), but only CRP and ESR were significantly associated with yearly IR. Conclusion: PMR relapse while tapering GC occurs frequently, and some – although weak – associations were found. Longer symptom duration before treatment decreased chance of relapse, but did not increase the amount of relapses per year of treatment, potentially indicating a more self-limiting disease course. A uniform definition of relapse and identifying further predictors for a potential prediction model is needed to focus GC sparing agents for patients. References: [1]Mackie SL et al. Can the prognosis of polymyalgia rheumatica be predicted at disease onset? Results from a 5-year prospective study. Rheumatology (Oxford). 2010;49(4):716–22. [2]Dejaco C et al. Current evidence for therapeutic interventions and prognostic factors in polymyalgia rheumatica: A systematic literature review informing the 2015 EULAR/ACR. ARD. 2015;74: 1808–17. Disclosure of Interests: None declared